An examination of class-based visibility bias in national child maltreatment reporting. (January 2018) - Kim, Hyunil; Drake, Brett; Jonson-Reid, Melissa
Abstract: It is widely assumed among researchers and policy makers that poverty increases children's exposure to professional reporters (e.g., social service providers) causing more reports to be made. This is sometimes called "Class-Based Visibility Bias" (CBVB) and the literature is consistent in placing this effect exclusively among professional reporters. To the degree that large CBVB effects exist, there must therefore be a higher proportion of reports from professionals as poverty increases. We examined this relationship using statewide individual-level data in four states (Idaho, Michigan, Missouri, and New Hampshire) and nationwide county-level data. Contrary to expectations, increasing poverty was not associated with increases in the proportions of reports from professionals in either individual- or county-level data. In fact, at both individual and county levels, there was a consistent tendency toward a slightly lower proportion of reports from professionals with increasing poverty, holding true across all racial/ethnic groups and maltreatment subtypes. We see two plausible explanations. First, it is theoretically possible that CBVB may be present both among professionals and nonprofessionals, but may be slightly stronger among nonprofessionals. This would require a fundamental reworking of existing CBVB theory, as there is no currently postulated rationale for why CBVB would apply to nonprofessionals such as families, friends, and neighbors. The second possible explanation is that CBVB is not a primary driver of official maltreatment reports, and that concerns about CBVB effects have been overblown. Given the recently emerging scientific consensus that the poverty/maltreatment relationship is largely real, and not a function of reporting bias, the second explanation may be more plausible. Highlights: Class Based Visibility Bias (CBVB) asserts that professionals over-report the poor. Empirical support for CBVB is currently lacking. We test for CBVB both nationally and within four states. We find no support for CBVB at the county or individual levels of analysis. The CBVB hypothesis either requires substantial revision or should be discarded.